High Prevalence of Hypovitaminosis D in Climacteric and Beyond in a Teaching Center from North Eastern India - Sharma, Dr Nalini; Das, Dr Rituparna; Ruram, Dr Alice Abraham; Panda, Dr Subrat (International Journal of Innovative Research in Medical Science, 2020)
Background: Data on the prevalence of hypovitaminosis D in peri and post menopausal tribal multiethnic Indians women living in the North Eastern part of the country are limited. Aim: To evaluate the vitamin D(VD) level in North Eastern multiethnic tribal perimenopausal and postmenopausal women Indian women. Material and Method: This prospective study was conducted at a tertiary care centre from 2018 to2019in North Eastern India Catering multiethnic tribal population. A total of498women above 40 years of age who attended gynae opd for various reasons were included in the study Women were advised to give 3 cc blood samples. The serum VD was estimated by Beckman Coulten Unicel DXI immunoassay system using the principle of chemiluminescence, Incidence of Vitamin D deficiency (VDD) and insufficiency (VDI) calculated. VDD was defined as 25(OH) D level in blood<20ng/ml and insufficiency of VD was defined as 25(OH) D levels <30ng/ml/. Result: In present study mean age was 46.78±6.914 years. 50.40%women were vitamin D deficient. 37.95% women were vitamin D insufficient. Mean parity was 3.94±9.23 and mean value of vit d was 21.36±9.23. Conclusion: Hypovitaminosis D is highly prevalent among perimenopausal and post menopausal women in the North eastern part of India. The need for improving the levels of vitamin D among this group of population is both vital and urgent.